Heavy metals and trace elements detected in the leaves of medicinal plants collected in the southeast part of Turkey - ÖZYİĞİT, İBRAHİM İLKER (SPRINGER HEIDELBERG, 2022)
The present study focused on the heavy metal and essential element contents that were detected in 37 different plants for making assessments to reveal possible heavy metal contamination and its effects on plant and human health. These plants having medicinal properties are used widely in the southeast part of Turkey. ICP-OES was employed for the determination of Al, B, Ca, Cd, Cr, Cu, Fe, K, Mg, Mn, Na, Ni, Pb, and Zn concentrations in the leaves of some selected medicinal plants. The concentration rates (in mg kg(-1)) obtained in ascending order were as in the following ranges: 8.68-278.83 for Al, 46.68-505.24 for B, 2430.0-15,561.3 for Ca, 0.04-1.11 for Cd, 0.94-21.67 for Cr, 13.7-44.81 for Cu, 12.1-456.2 for Fe, 1083.3-9026.98 for K, 344.8-3064.72 for Mg, 48.32-557.62 for Mn, 295.38-1416.02 for Na, 0.042-9.58 for Ni, 1.37-18.0 for Pb, and 68.82-220.29 for Zn. The plants collected from the sites that were located in close proximity to industrial and mining areas as well as farming fields were found to contain higher heavy metal concentrations. Our findings demonstrated that necessary precautions must be taken into consideration for saving the fields from heavy metal contamination where medicinal plants are grown or collected. Otherwise, it shows that these plants could pose risk to human health.
Keywords: Bioaccumulation; Ethnobotany; Heavy metal contamination; Trace elements; RDA value; ETHNOBOTANICAL SURVEY; RISK-ASSESSMENT; HERBAL TEAS; MANGANESE; HEALTH; L.; ACCUMULATION; CADMIUM; PHYTOREMEDIATION; BIOMONITOR